Hubungan Usia, Jumlah Paritas, dan Obesitas dengan Kejadian Mioma Uteri di RS Ibnu Sina Makassar - Afdalia Amanda; Rauly Rahmadhani; Abd. Rahman; Sari Ifdiana Jalal; Abd. Rahim Yunus (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Reproductive health is an important issue that affects women's well-being. One issue is uterine myoma. This study aims to analyze the relationship between age, parity, obesity, and the incidence of uterine myoma at Ibnu Sina Hospital in Makassar. The study employed a descriptive, quantitative, cross-sectional design and involved 106 respondents selected from medical records using purposive sampling. The data were analyzed using the chi-square test in SPSS version 29. The results showed no significant differences in age (p=0.245),  parity (p=0.279), or obesity (p=0.845) between women with and without uterine myoma. In conclusion, no relationship was found between these three factors and the incidence of uterine myoma at Ibnu Sina Hospital in Makassar.